Flow-synchronized nasal intermittent positive pressure ventilation in the preterm infant: development of a project - Corrado Moretti; Paola Papoff; Camilla Gizzi; Francesco Montecchia; Luigi Giannini; Carla Fassi; Fabio Midulla; Rocco Agostino; Manuel Sanchez-Luna (Journal of Pediatric and Neonatal Individualized Medicine, 2013)
This manuscript describes the experience of our team in developing a flow-triggered nasal respiratory support for the neonate and its related clinical applications. Although mechanical ventilation (MV) via an endotracheal tube has undoubtedly led to improvement in neonatal survival in the last 40 years, the prolonged use of this technique may predispose the infant to the development of many possible complications, first of all, bronchopulmonary dysplasia (BPD). Avoiding mechanical ventilation is thought to be a critical goal, and different modes of non invasive respiratory support may reduce the intubation rate: nasal continuous positive airway pressure (NCPAP), nasal intermittent positive pressure ventilation (NIPPV) and its more advantageous form, synchronized nasal intermittent positive pressure ventilation (SNIPPV). SNIPPV was initially performed by a capsule placed on the baby’s abdomen. To overcome the disadvantages of the abdominal capsule, our team decided to create a flow-sensor that could be interposed between the nasal prongs and the Y piece. Firstly we developed a hot-wire flow-sensor to trigger the ventilator and we showed that flow-SNIPPV can support the inspiratory effort in the post-extubation period more effectively than NCPAP. But, although accurate, the proper functioning of the hot-wire flow-sensor was easily compromised by secretions or moisture, and therefore we started to use as flow-sensor a simpler differential pressure transducer. In a following trial using the new device, we were able to demonstrate that flow-SNIPPV was more effective than conventional NCPAP in decreasing extubation failure in preterm infants who had been ventilated for respiratory distress syndrome (RDS). More recently we used flow-SNIPPV as the primary mode of ventilation, after surfactant replacement, reducing MV need and favorably affecting short-term morbidities of treated premature infants. We also successfully applied SNIPPV to treat apnea of prematurity (AOP). Finally, we developed a new shaped flow-sensor, which is smaller and lighter of the previous one and its reliability was tested using a simulated neonatal model.